Reclaiming to Brackish Wetlands in the Alberta Oil Sands: Comparison of Responses to Sodium Concentrations by Carex atherodes and Carex aquatilis - Lilyan C. Glaeser; Melissa House; Dale H. Vitt (Plants, 2021)
The variation in sodium concentrations in waters of natural fens and marshes on the western Canadian landscape provides a background for choosing the appropriate plants for wetland reclamation. Broad tolerances to salinity are especially important for reclamation trials on saline-rich ‘in-pits’ that were left from open-pit oil sands mining. One such species, Carex aquatilis, has been identified as a key species in early reclamation attempts; however, at the Sandhill Wetland on the Syncrude Canada oil sands lease, this species has aggressively colonized, dominating parts of the wetland and limiting species diversity. A second species, also widespread on natural lake shores and marshes, is Carex atherodes, with field observations suggesting a broad tolerance to salinity. Here, we examine the responses of this species to a series of sodium concentrations and compare these to those of C. aquatilis. In particular, we addressed three questions: (1) How do structural attributes of C. atherodes respond to a series of Na+ concentration treatments? (2) Are different structural responses related to the functional attributes of photosynthesis, stomatal conductance, and/or transpiration rate? (3) How do these responses compare to those of C. aquatilis? We implemented a phytotron experiment to test the responses of these two species to either five or six concentrations of sodium, ranging from 20 to 3000 mg Na+ L−1. In general, structural responses of C. atherodes did not differ between 50 and 789 mg Na+ L−1, while performances of all attributes were reduced at 1407 mg L−1. Physiological attributes had high variation, but also had reduced performances at similar treatment levels. In comparison, a clear threshold was present for structural attributes in Carex aquatilis between 1650 and 2148 mg Na+ L−1, while physiological attributes were reduced between 1035 to 1650 mg Na+ L−1. These responses from C. aquatilis were similar to those previously reported. Na+ concentrations in porewater at the Sandhill Wetland in 2019 reached as ...